Overexpression of the Zygophyllum xanthoxylum Aquaporin, ZxPIP1;3, Promotes Plant Growth and Stress Tolerance - Li, Mengzhan (Int J Mol Sci, 2021)
Drought and salinity can result in cell dehydration and water unbalance in plants, which seriously diminish plant growth and development. Cellular water homeostasis maintained by aquaporin is one of the important strategies for plants to cope with these two stresses. In this study, a stress-induced aquaporin, ZxPIP1;3, belonging to the PIP1 subgroup, was identified from the succulent xerophyte Zygophyllum xanthoxylum. The subcellular localization showed that ZxPIP1;3-GFP was located in the plasma membrane. The overexpression of ZxPIP1;3 in Arabidopsis prompted plant growth under favorable condition. In addition, it also conferred salt and drought tolerance with better water status as well as less ion toxicity and membrane injury, which led to more efficient photosynthesis and improved growth vigor via inducing stress-related responsive genes. This study reveals the molecular mechanisms of xerophytes’ stress tolerance and provides a valuable candidate that could be used in genetic engineering to improve crop growth and stress tolerance.